1997
DOI: 10.1046/j.1365-201x.1997.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after myocardial infarction and cardiac arrest in rats: role of ANP‐induced albuminuria?

Abstract: Renal function was measured by clearance technique before and after acute myocardial infarction (MI) induced by left coronary artery ligation in male Sprague-Dawley rats. The animals were anaesthetized with halothane-nitrous oxide, paralysed with pancuronium and artificially ventilated. All parameters were stable throughout the experiment in sham-operated time control animals (n = 8). After MI, rats developed left ventricular dysfunction with increased left ventricular end-diastolic pressure and decreased mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Previous studies have indeed demonstrated that systemic ANP infusion in anesthetized rats can markedly increase urinary albumin excretion, although the exact mechanisms of this proteinuric action have not been elucidated (22). The direct assessment of glomerular permeability in the present study supports the concept that ANPinduced albuminuria is a consequence of a direct effect on the glomerular filtration barrier, leading to a partly reversible increase in the radius and number of large glomerular pores without any primary effects on glomerular charge selectivity.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies have indeed demonstrated that systemic ANP infusion in anesthetized rats can markedly increase urinary albumin excretion, although the exact mechanisms of this proteinuric action have not been elucidated (22). The direct assessment of glomerular permeability in the present study supports the concept that ANPinduced albuminuria is a consequence of a direct effect on the glomerular filtration barrier, leading to a partly reversible increase in the radius and number of large glomerular pores without any primary effects on glomerular charge selectivity.…”
Section: Discussionsupporting
confidence: 75%
“…From the data of Tucker et al (34), we could calculate that an iv ANP infusion rate of 800 ng·kg Ϫ1 ·min Ϫ1 would produce a plasma concentration of 1,740 pg/ml, which is in the (lower) range of 2,000 -3,000 pg/ml, which have been observed after 25% blood volume expansion in rats with experimental heart failure (10), but higher than observed after 20% plasma volume expansion in rats by another group (24). Furthermore, 800 ng·kg Ϫ1 ·min Ϫ1 is about intermediate between the medium and the high doses of ANP infused in rats for studies of ANP-induced albuminuria by Nielsen et al (22).…”
Section: Animals and Surgery Experiments Were Performed In 34 Malementioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of OT is first attributable to its negative chronotropic and inotropic roles in cardiac activity following the activation of cardiac OTR (Costa E Sousa et al, 2005) in association with the release of protective atrial natriuretic peptide (ANP) and nitric oxide (NO) (Houshmand et al, 2015) and increase in parasympathetic output (Sun et al, 2015), decrease in the activity of renin-angiotensin-aldosterone system (Nielsen et al, 1997) and reduction of sympathetic outflow (Olszewski et al, 2010). In addition, OT also decreased cardiac preload and afterload through its diuresis and natriuretic effect (Nielsen et al, 1997). As a result, OT can reduce oxygen consumption while increasing the cardiac output during I/R injury.…”
Section: Atherosclerosis and Cardioprotective Effect Of Otmentioning
confidence: 99%
“…In our studies, surgical denervation produces a consistent reduction of renal norepinephrine concentration of this magnitude (V; Spannow et ul. 1997;Nielsen et al 1997).…”
Section: Renal Denervationmentioning
confidence: 99%